The use of HPV Linear Array Assay for multiple HPV typing on archival frozen tissue and DNA specimens - Woo, Y.L.; Damey, I.; Stanley, M.; Crawford, R.; Sterling, J. (Elsevier, 2007)
Accurate HPV typing is important for natural history and epidemiology studies. With the introduction of prophylactic multivalent HPV vaccines, there is also the need to determine the dominant genotypes in different populations and the effect of a vaccination programme on infection profiles. The interplay between multiple infection, viral persistence and implementation of interventions is a complicated one and therefore requires a reliable and accurate HPV detection and typing method. The Linear Array HPV genotyping test is a PCR-based HPV detection kit which can detect qualitatively Multiple HPV Infection in cervical cells collected in PreservCyt® Solution. The utility of this kit for multiple HPV typing of archival frozen tissue and cervical cells not collected in PreservCyt® are described.